Early microglial response, myelin deterioration and lethality in mice deficient for very long chain ceramide synthesis in oligodendrocytes. Issue 4 (30th December 2022) - Teo, Jonathan D.; Marian, Oana C.; Spiteri, Alanna G.; Nicholson, Madeline; Song, Huitong; Khor, Jasmine X. Y.; McEwen, Holly P.; Ge, Anjie; Sen, Monokesh K.; Piccio, Laura; Fletcher, Jessica L.; King, Nicholas J. C.; et al.
Abstract: The sphingolipids galactosylceramide (GalCer), sulfatide (ST) and sphingomyelin (SM) are essential for myelin stability and function. GalCer and ST are synthesized mostly from C22‐C24 ceramides, generated by Ceramide Synthase 2 (CerS2). To clarify the requirement for C22‐C24 sphingolipid synthesis in myelin biosynthesis and stability, we generated mice lacking CerS2 specifically in myelinating cells (CerS2 ΔO/ΔO ). At 6 weeks of age, normal‐appearing myelin had formed in CerS2 ΔO/ΔO mice, however there was a reduction in myelin thickness and the percentage of myelinated axons. Pronounced loss of C22‐C24 sphingolipids in myelin of CerS2 ΔO/ΔO mice was compensated by greatly increased levels of C18 sphingolipids. A distinct microglial population expressing high levels of activation and phagocytic markers such as CD64, CD11c, MHC class II, and CD68 was apparent at 6 weeks of age in CerS2 ΔO/ΔO mice, and had increased by 10 weeks. Increased staining for denatured myelin basic protein was also apparent in 6‐week‐old CerS2 ΔO/ΔO mice. By 16 weeks, CerS2 ΔO/ΔO mice showed pronounced myelin atrophy, motor deficits, and axon beading, a hallmark of axon stress. 90% of CerS2 ΔO/ΔO mice died between 16 and 26 weeks of age. This study highlights the importance of sphingolipid acyl chain length for the structural integrity of myelin, demonstrating how a modest reduction in lipid chain length causes exposure of a denatured myelin protein epitope and expansion of phagocytic microglia, followed by axon pathology, myelin degeneration, and motor deficits. Understanding the molecular trigger for microglial activation should aid the development of therapeutics for demyelinating and neurodegenerative diseases. Main Points: Oligodendrocytes lacking CerS2 produce myelin using sphingolipids with C16/C18 instead of C22/C24 N‐acyl chains. C22/C24 myelin sphingolipids are essential for myelin stability, microglial quiescence, and survival beyond young adulthood.